Life Skills with teenagers: An itinerary of School and Educational Psychology (Research, Society and Development, 2023)
The empowerment of adolescents is part of one of the itineraries of School and Educational Psychology for health care and well-being. In our country, education is oriented towards performance and not towards adolescents and their development as skills that enable them to live effectively in this world. The objective is to present a professional experience report on Skills for Life with a group of teenagers from basic education in a public school. Having life skills implies preventing behaviors such as early pregnancy, substance abuse, reducing the risk of chronic noncommunicable diseases [NCDs] and strengthening self-esteem and a culture of peace. The meetings take place from the perspective of thematic groups in the light of Bandura's Theory of Social Learning. Through an active methodology, the ten Skills for Life themes are structured. With this practice, the possibility of building a doing and a doing in Psychology and Education is evident, both involved in the promotion and recovery of the health and well-being of schoolchildren after the legacy left by the Covid-19 pandemic.